2019
DOI: 10.3390/ijms20246211
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Tumor-Induced Osteoclastogenesis Pathway Insensitive to Denosumab but Interfered by Cannabidiol

Abstract: Bone metabolism is strictly regulated, and impaired regulation caused by hormonal imbalances induces systemic bone loss. Local bone loss caused by tumor invasion into bone is suggested to be induced by the generation of cytokines, which affect bone metabolism, by tumor cells. The major cause of systemic and local bone losses is excess bone resorption by osteoclasts, which differentiate from macrophages by receptor activator of nuclear factor kappa-B ligand (RANKL) or tumor necrosis factor-alpha (TNF-α). We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Histopathological findings of OSCC cases with in the bone reveal the interposition of fibrous stromal tissue between cancer c surfaces. Culture supernatants of OSCC cells revealed osteoclastogenesis w with OPCs, and we identified the cause as secreted vesicles or certain solu the previous study, we showed that extracellular microvesicles secreted fro that had osteoclastogenic properties induced osteoclastogenesis when suppl OPC cultures [28]. Notably, the depletion of extracellular microvesicles fro supernatant significantly decreased the osteoclastogenic activity, but not co Hence, to search for other candidates, we analyzed soluble factors secreted b Among numerous soluble factors, some inflammatory cytokines have b stimulate osteoclastogenesis [21].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Histopathological findings of OSCC cases with in the bone reveal the interposition of fibrous stromal tissue between cancer c surfaces. Culture supernatants of OSCC cells revealed osteoclastogenesis w with OPCs, and we identified the cause as secreted vesicles or certain solu the previous study, we showed that extracellular microvesicles secreted fro that had osteoclastogenic properties induced osteoclastogenesis when suppl OPC cultures [28]. Notably, the depletion of extracellular microvesicles fro supernatant significantly decreased the osteoclastogenic activity, but not co Hence, to search for other candidates, we analyzed soluble factors secreted b Among numerous soluble factors, some inflammatory cytokines have b stimulate osteoclastogenesis [21].…”
Section: Discussionmentioning
confidence: 63%
“…Culture supernatants of OSCC cells revealed osteoclastogenesis when cultured with OPCs, and we identified the cause as secreted vesicles or certain soluble factors. In the previous study, we showed that extracellular microvesicles secreted from OSCC cells that had osteoclastogenic properties induced osteoclastogenesis when supplemented with OPC cultures [28]. Notably, the depletion of extracellular microvesicles from the culture supernatant significantly decreased the osteoclastogenic activity, but not completely [28].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“… 54 , 55 There is also evidence that CBD can suppress osteoclastogenesis and reduce the function of human osteoclasts. 56 , 57 …”
mentioning
confidence: 99%